2009
DOI: 10.1177/0021998309345304
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Morphology and Thermomechanical Behavior of Polyethylene Glycol/1,8-Octanediol-modified Epoxy-organoclay Hybrid Nanocomposites

Abstract: Organoclay-filled polyethylene glycol (PEG)/1,8-octanediol (OCT)-modified epoxy matrices were developed. Epoxy systems modified with 10, 20, and 30 wt% of PEG/OCT were made by using diglycidyl ethers of bisphenol A epoxy resin and PEG/OCT with 4,4 0 -diaminodiphenylmethane as curing agent. The PEG/OCT-modified epoxy systems were further modified with 1, 3, and 5 wt% of organoclay. The thermal behavior of organoclay-filled PEG/OCT-modified epoxy matrices were characterized using differential scanning calorimete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Due to the presence of flexible ether linkages, polyethylene glycol (PEG) is expected to increase the toughness of epoxy resin. Chozhan et al [ 177 ] reported that epoxy nanocomposites modified with PEG and/or octanediol (OCT) exhibited improved mechanical properties. The impact and tensile strengths of epoxy composites containing 3 wt% organoclay and 20 wt% PEG or 3 wt% organoclay and 10 wt% OCT were increased by 95% and 30%, respectively, compared to the neat epoxy.…”
Section: Hybrid Epoxy Nanocompositesmentioning
confidence: 99%
“…Due to the presence of flexible ether linkages, polyethylene glycol (PEG) is expected to increase the toughness of epoxy resin. Chozhan et al [ 177 ] reported that epoxy nanocomposites modified with PEG and/or octanediol (OCT) exhibited improved mechanical properties. The impact and tensile strengths of epoxy composites containing 3 wt% organoclay and 20 wt% PEG or 3 wt% organoclay and 10 wt% OCT were increased by 95% and 30%, respectively, compared to the neat epoxy.…”
Section: Hybrid Epoxy Nanocompositesmentioning
confidence: 99%
“…16 1,8-Octanediol (OD) is the largest water-soluble aliphatic diol, with no reported toxicity 17 and eight methylene groups on its main chain. 18 However, its polarity is obviously weaker than that of the previously mentioned polyol-based plasticizers. In addition, the existence of hydroxyl groups at both ends ensures that OD interacts well with protein chains.…”
Section: Introductionmentioning
confidence: 95%
“…However, those common plasticizers are highly hydrophilic and hygroscopic, leading to significant increases in the water vapor permeability of films . 1,8‐Octanediol (OD) is the largest water‐soluble aliphatic diol, with no reported toxicity and eight methylene groups on its main chain . However, its polarity is obviously weaker than that of the previously mentioned polyol‐based plasticizers.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important thermosetting resins, epoxy resins are usually used as adhesives, coatings, and matrices in many engineering materials due to their high mechanical properties, excellent adhesion to various substrates, and good thermal and dimensional stability. In addition, epoxy resin can be cured to form network structures on the surface or inside of the wood, which not only protects the wood from decay fungi but also improves the dimensional stability and mechanical properties of wood. The use of epoxy resins in enhancing the properties of wood has received increasing attention in recent years. As the high viscosity of the normal epoxy has difficulty in penetrating the wood, an organic solvent such as acetone is usually introduced to allow easier impregnation .…”
Section: Introductionmentioning
confidence: 99%